The Pseudomonas putida HskA hybrid sensor kinase controls the composition of the electron transport chain. Issue 2 (6th December 2012) - Sevilla, Emma; Silva‐Jiménez, Hortencia; Duque, Estrella; Krell, Tino; Rojo, Fernando
Summary: Sensor kinases play a key role in sensing and responding to environmental and physiological signals in bacteria. In this study we characterized a previously unknown orphan hybrid sensor kinase from Pseudomonas putida, which is conserved in several Pseudomonads. Inactivation of the gene coding for this sensor kinase, which we have named HskA, modified the expression of at least 85 genes in cells growing in a complete medium. HskA showed a strong influence on the composition of the electron transport chain. In cells growing exponentially in a complete medium, the absence of HskA led to a significant reduction in the expression of the genes coding for the bc1 complex and for the CIO and Cbb3‐1 terminal oxidases. In stationary phase cells, however, lack of HskA caused a higher expression of the Cyo terminal oxidase and a lower expression of the Aa3 terminal oxidase. The HskA polypeptide shows two PAS (signal‐sensing) domains, a transmitter domain containing the invariant phosphorylatable histidine and an ATP binding site, and a receiver domain containing the conserved aspartate capable of transphosphorylation, but lacks an Hpt module. It is therefore a hybrid sensor kinase. Phosphorylation assays showed that purified HskA undergoes autophosphorylation in the presence of ATP.